2004
DOI: 10.1111/j.1468-4446.2004.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

The sources of political orientations in post‐industrial society: social class and education revisited

Abstract: This paper studies the impact of social class and education on political orientation. We distinguish the 'old' middle class from a new class of social/cultural specialists. However, the difference in their political orientation may especially be related to the level and field of education; the new middle class is more highly educated and often in fields of study that extensively address social competencies, characteristics independently affecting political outcomes. Analyses on Dutch data showed that education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 28 publications
7
97
0
1
Order By: Relevance
“…Early studies of political behaviour demonstrated that education has a direct positive impact on political and social participation, by enhancing citizens' psychological engagement and by providing them with the cultural instruments necessary to orientate themselves in the complex political world (Hyman and Wright, 1979, Van de Werfhorst and De Graaf, 2004and Weakliem, 2002. On this line, the low levels of education in Italian society in the late 1950s were considered responsible for a lack of political skills, necessary to become a participatory citizen (e.g.…”
Section: Education System Support and System Criticismmentioning
confidence: 94%
“…Early studies of political behaviour demonstrated that education has a direct positive impact on political and social participation, by enhancing citizens' psychological engagement and by providing them with the cultural instruments necessary to orientate themselves in the complex political world (Hyman and Wright, 1979, Van de Werfhorst and De Graaf, 2004and Weakliem, 2002. On this line, the low levels of education in Italian society in the late 1950s were considered responsible for a lack of political skills, necessary to become a participatory citizen (e.g.…”
Section: Education System Support and System Criticismmentioning
confidence: 94%
“…competences) separately. Citizenship orientations are combinations of knowledge, attitudes and skills and thus the perspectives on citizenship underlying these (Almond and Verba 1989;Janmaat 2007;Qinghua 2002;Werfhorst and de Graaf 2004). One such orientation, for example, may entail attitudes reflecting a willingness to participate in a community, the skills needed for proper participation in that community and critical reflection on issues of relevance for participation in the community (e.g.…”
Section: Citizenship Orientations and The Purpose Of The Present Studymentioning
confidence: 99%
“…While previous research has recurrently shown that, in general, retirement positively influences volunteering (Chambré, 1984;Choi, 2003;Erlinghagen & Hank, 2006;Hank & Erlinghagen, 2009;Mutchler, Burr, & Caro, 2003;Principi, Warburton, Schippers, & Di Rosa, 2012;van den Bogaard, Henkens, & Kalmijn, 2014), there are good reasons to suspect that this effect differs for people from various backgrounds. In social stratification research, the question whether is it mostly human capital or rather class that is at work as a differentiating factor in society has been debated extensively.…”
Section: Introductionmentioning
confidence: 93%
“…It has been argued that cultural resources, like cognitive skills and knowledge, have become dominant over traditional class hierarchies for explaining differences between people (Bell, 1976;Bourdieu, 1984;Brint, 1984;Gouldner, 1979;Pakulski & Waters, 1996). The relative importance of education over occupation has also been attested empirically, mostly for values and attitudes (Davis, 1982;Kalmijn & Kraaykamp, 2007;Svallfors, 2005;Van de Werfhorst & De Graaf, 2004). On the other hand, there are those who maintain that the class position of a person, usually measured by their occupation, remains the principal component (Evans, 1993;Goldthorpe & Marshall, 1992;Hout, Brooks, & Manza, 1993).…”
Section: Introductionmentioning
confidence: 99%